Transportation Infrastructure Optimization for Enchancing Disaster Preparedness in The Sepaku Semoi Dam Emergency Plan (EAP) - Zony Yulfadli; Tukimun Tukimun; Friska Feronica Bn Putri; Abul Hashem Beg (UIN Sumatera Utara, 2025)
This study examines the optimization of evacuation routes within the Emergency Action Plan (EAP) for the Sepaku Semoi Dam in East Kalimantan, Indonesia, through the application Analytical Hierarchy Process (AHP). The analysis was based on three key criteria : accesibility (0.45), road capacity ( 0.30) and physical resilience (0.25). The evaluation was carried out utilizing expert questionnaires (n = 80), field surveys, and secondary data, which encompassed HEC-RAS flood simulations and the official Emergency Action Plan (RTD) document. The results underscore the Silkar-Bukit Raya-Petung corridor (A1) as the most reliable evacuation route, succeeded by the Trans Kalimantan Road (A2) and the Southern Ring Road (A3), whereas the Karang Jinawi-Sotek Road (A4) plays a supplementary role for areas with high population density. Furthermore, two additional routes (A5 and A6) are suggested as qualitative extensions to the network, which are not part of the AHP ranking, aimed at enhancing spatial coverage for underserved communities. The estimation of the evacuation fleet suggests that around 23,700 residents would need transportation in the event of a dam failure. The combination of AHP with spatial and survey-based data establishes a systematic and replicable framework for prioritizing evacuation routes in the context of dam-related disaster preparedness.